Rancang Bangun E-Learning Di SMA Negeri 8 Bogor - Saputra, Sopandi (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
SMAN 8 Bogor, which is located in the city of Bogor, is one of the schools that use conventional learning methods, which can only be done with the condition of meeting between students and teachers in the classroom. So that we need a new system that can support teaching and learning activities. The system built is a web-based online learning information system (e-learning) wherein there is a feature in this system for distributing materials, assignments, problem exercises, tutorials and information- other information related to school activities, so that it is expected to help students' learning activities because with this system, students can access learning activities anywhere not only in the classroom.